Perspective: Stepping Stones to Unraveling the Pathophysiology of Mal de Debarquement Syndrome with Neuroimaging - Mucci, Viviana; Cha, Yoon-Hee; Wuyts, Floris L.; Van Ombergen, Angelique (Frontiers in Neurology, 2018)
Mal de debarquement syndrome (MdDS) is a neurological condition typically characterized by a sensation of motion, which in most cases manifests after disembarking from a vehicle (e.g., boat, plane, and car). However, the same symptoms can also occur spontaneously. Two main theories of the pathophysiology of MdDS are briefly summarized here. In this perspective, we aimed to report the most recent findings on neuroimaging studies related to MdDS, as well as to suggest further potential research questions that could be addressed with the use of neuroimaging techniques. A detailed analysis of previous work on MdDS has led to five main research questions that could be addressed in new neuroimaging studies. Furthermore, in this perspective, we propose new stepping-stones to addressing critical research questions related to MdDS and its pathophysiology. We propose considerations for new studies, as well as a detailed analysis of the current limitations and challenges present when studying MdDS patients. We hope that our examination of the nuances of MdDS as a neurological disorder will contribute to more directed research on this topic.